Learning styles favoured by professional, amateur, and recreational athletes in different sports - González-Haro, C.; Calleja-Gonzalez, J.; Escanero, J. F. (Journal of Sports Sciences, 2010)
The aim of this study was to characterize the learning styles of different groups of athletes grouped according to level of performance and sport. Seventy-one male athletes completed a questionnaire on learning styles at the beginning of the 2008-2009 training season. Learning styles were assessed using the Honey-Alonso Learning Styles Questionnaire, and were also converted into learning styles described by Kolb. The Honey-Alonso learning styles were compared among the various groups using one-way analysis of variance, and the Kolb learning styles that were most favoured using a chi-square test. Pearson's correlation coefficient was used to verify the relationships between variables. No significant differences were observed in learning styles between different sports and physical activities. Years of experience did not correlate strongly with learning styles. With respect to level of performance, the pragmatic component was significantly lower in professional athletes than amateur and recreational athletes. These characteristics of learning styles preferred by the athletes should help coaches and physical trainers to reflect on their role as educators in the context of planning sports training.